(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Given the economic and social repercussions of unemployment, this study aims to measure the relative impact (elasticity) of the most significant determinants of unemployment in Saudi Arabia, using econometric analysis over the period 2000–2024. The study reveals that the majority of employees in the public sector are Saudi nationals, whereas expatriate workers are concentrated in the private sector. The unemployment rate in Saudi Arabia ranged from a low of 3.5% in 2024 to a high of 7.7% in 2020, with an average annual rate of 5.51% during the study period. The female unemployment rate was higher than the male rate, as male unemployment decreased by 2.7%, while female unemployment increased by 1.9% during the period 2000–2024. The findings show that a 10% increase in both the domestic investment rate and the ratio of Saudi to expatriate workers leads to reductions in unemployment of 9.1% and 3.4%, respectively. Conversely, a 10% increase in inflation (implicit deflator) results in a 10.6% rise in unemployment. Despite the Kingdom’s success in reducing the female unemployment rate from 35.7% in 2012 to 13.1% in 2024, the Ministry of Human Resources and Social Development remains committed to further lowering unemployment in line with Saudi Vision 2030 by expanding training programs and aligning them with available labor-market opportunities.